Recurrent activating mutation in PRKACA in cortisol-producing adrenal tumors. - Goh, Gerald; Scholl, Ute I; Healy, James M; Choi, Murim; Prasad, Manju L; Nelson-Williams, Carol; Kunstman, John W; Kuntsman, John W; Korah, Reju; Suttorp, Anna-Carinna; Dietrich, Dimo; Haase, Matthias; et al. (Nat Genet, 2014)
Adrenal tumors autonomously producing cortisol cause Cushing's syndrome. We performed exome sequencing of 25 tumor-normal pairs and identified 2 subgroups. Eight tumors (including three carcinomas) had many somatic copy number variants (CNVs) with frequent deletion of CDC42 and CDKN2A, amplification of 5q31.2 and protein-altering mutations in TP53 and RB1. Seventeen tumors (all adenomas) had no somatic CNVs or TP53 or RB1 mutations. Six of these had known gain-of-function mutations in CTNNB1 (β-catenin) or GNAS (Gαs). Six others had somatic mutations in PRKACA (protein kinase A (PKA) catalytic subunit) resulting in a p.Leu206Arg substitution. Further sequencing identified this mutation in 13 of 63 tumors (35% of adenomas with overt Cushing's syndrome). PRKACA, GNAS and CTNNB1 mutations were mutually exclusive. Leu206 directly interacts with the regulatory subunit of PKA, PRKAR1A. Leu206Arg PRKACA loses PRKAR1A binding, increasing the phosphorylation of downstream targets. PKA activity induces cortisol production and cell proliferation, providing a mechanism for tumor development. These findings define distinct mechanisms underlying adrenal cortisol-producing tumors.
Keywords: Adolescent; Adrenal Gland Neoplasms; Adult; Aged; Amino Acid Sequence; Base Sequence; cdc42 GTP-Binding Protein; Cell Proliferation; Cyclic AMP-Dependent Protein Kinase Catalytic Subunits; Cyclin-Dependent Kinase Inhibitor p16; DNA Copy Number Variations; Exome; Female; Gene Deletion; Gene Dosage; HEK293 Cells; Humans; Hydrocortisone; Male; Middle Aged; Molecular Sequence Data; Mutation; Phosphorylation; Sequence Analysis, DNA; Sequence Homology, Amino Acid

Somatic and germline CACNA1D calcium channel mutations in aldosterone-producing adenomas and primary aldosteronism. - Scholl, Ute I; Goh, Gerald; Stölting, Gabriel; de Oliveira, Regina Campos; Choi, Murim; Overton, John D; Fonseca, Annabelle L; Korah, Reju; Starker, Lee F; Kunstman, John W; Prasad, Manju L; Hartung, Erum A; et al. (Nat Genet, 2013)
Adrenal aldosterone-producing adenomas (APAs) constitutively produce the salt-retaining hormone aldosterone and are a common cause of severe hypertension. Recurrent mutations in the potassium channel gene KCNJ5 that result in cell depolarization and Ca(2+) influx cause ∼40% of these tumors. We identified 5 somatic mutations (4 altering Gly403 and 1 altering Ile770) in CACNA1D, encoding a voltage-gated calcium channel, among 43 APAs without mutated KCNJ5. The altered residues lie in the S6 segments that line the channel pore. Both alterations result in channel activation at less depolarized potentials; Gly403 alterations also impair channel inactivation. These effects are inferred to cause increased Ca(2+) influx, which is a sufficient stimulus for aldosterone production and cell proliferation in adrenal glomerulosa. We also identified de novo germline mutations at identical positions in two children with a previously undescribed syndrome featuring primary aldosteronism and neuromuscular abnormalities. These findings implicate gain-of-function Ca(2+) channel mutations in APAs and primary aldosteronism.
Keywords: Adrenal Cortex Neoplasms; Adrenocortical Adenoma; Aldosterone; Amino Acid Sequence; Calcium Channels, L-Type; Cell Line; Child; Child, Preschool; Female; Germ-Line Mutation; Humans; Hyperaldosteronism; Male; Molecular Sequence Data; Mutation; Pedigree; Protein Conformation; Sequence Alignment